PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, LINGKUNGAN SEKOLAH DAN KEPUASAN KERJA GURU TERHADAP KOMITMEN GURU - Rieke Febrina; Marwan Marwan; Diding Nurdin (Hijri, 2025)
This study aims to analyze the influence of Principal Leadership, School Environment, and Teacher Satisfaction on Teacher Commitment in State Vocational High Schools (SMKs) in Aceh Tenggara Regency. The research employs a quantitative approach with a survey method, involving 152 teachers from 6 State SMKs as the sample, selected using a cluster random sampling technique. Data were collected through a questionnaire based on a 5-point Likert scale and analyzed using multiple linear regression and classical assumption tests. The results indicate that all independent variables (Principal Leadership, School Environment, and Teacher Satisfaction) significantly influence Teacher Commitment. Collectively, these three variables explain 44.4% of the variation in Teacher Commitment. The ANOVA test confirms that the regression model used is significant at a 99% confidence level (p < 0.01). The study concludes that enhancing teacher commitment requires attention to effective leadership, creating a conducive school environment, and improving teacher job satisfaction. These findings hold important implications for policymaking in the education sector, particularly in improving the quality of teaching in underdeveloped areas like Aceh Tenggara.